Inheritance for ToLCV and EB resistance in tomato using S. habrochaites and S. pimpinellifolium (Current Horticulture, 2024)
Two accessions of wild species of tomato, viz. EC-520060 (Solanum habrochaites) and EC-521080 (Solanum pimpinellifolium) have been utilized for introgression of ToLCV and EB resistant gene into 12 susceptible cultivars bearing good yield traits. Most of the crosses of EC-520060 exhibited 13 (resistant): 3 (susceptible) genetic ratio but 'Flora Dade × EC-520060' expressed 3:1 genetic ratio. The crosses of EC-521080 have diverse genetic ratio of 1:2:1, 3:1 and 1:3. In result of inheritance of EB, the crosses of EC-520060 revealed 3:1 genetic ratio, and the crosses of EC-521080 represented 1:3, 1:2:1 and 3:1 genetic ratio. The crosses of EC-520060 and EC-521080 showed additive, dominance × dominance and additive × additive genetic models for both ToLCV and EB diseases. The inheritance among crosses and genetics of variables can be utilized for improvement of resistant tomato.
Keywords: Tomato; Interspecific crosses; Resistance; ToLCV; EB; Genetics